REALITAS KONFLIK RUMAH TANGGA DALAM FILM DUA HATI BIRU KARYA GINA S.NOER - Tia Dwi Octafiani; Mila Roysa; Sri Surachmi W (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
ABSTRACT The research, Social Critique of Domestic Conflict in the Film Dua Hati Biru by Gina S. Noer: A Feminist Review is motivated by the unequal gender relations within households resulting from patriarchal culture. Film, as a modern literary medium, is not only entertaining but also conveys social critique. The research problem encompasses the forms of social critique in domestic conflict and the feminist perspective on such conflict. This study aims to describe social critique and analyze domestic conflict through a feminist perspective. The theoretical basis uses Sugihastuti's feminist literary criticism, which encompasses subordination, stereotypes, patriarchy, power relations, double burdens, and marginalization, and is reinforced by Mansour Fakih's radical feminism, which positions patriarchy as the root of gender inequality. The research method is qualitative with content analysis. Data consist of dialogue, scenes, and film narrative. Data collection techniques include observation, note-taking, and documentation, while data analysis involves data reduction, presentation, and drawing conclusions. The results demonstrate a social critique of unequal roles, economic pressure, lack of communication, and family interference. A feminist review reveals subordination, stereotypes, double burdens, marginalization, and patriarchal domination within the household. In conclusion, the film Dua Hati Biru depicts gender inequality within families due to patriarchal culture. It is recommended that further research examine more diverse subjects and approaches.